Muscle fibre types and size distribution in sub-antarctic notothenioid fishes - Fernandez, D A; Calvo, J; Franklin, C E; Johnston, I A (2000)
The presumptive tonic muscles fibres of Cottoperca gobio, Champsocephalus esox, Harpagifer bispinis, Eleginops maclovinus, Patagonothen tessellata, P. cornucola and Paranotothenia magellanica stained weakly or were unstained for glycogen, lipid, succinic dehydrogenase (SDHase) and myosin ATPase (mATPase) activity. Slow, intermediate and fast twitch muscle fibres, distinguished on the basis of the pH stability of their mATPases, showed intense, moderate and low staining activity for SDHase, respectively. Slow fibres were the major component of the pectoral fin adductor profundis muscle. The proportion of different muscle fibre types varied from the proximal to distal end of the muscle, but showed relatively little variation between species. The myotomes contained a lateral superficial strip of red muscle composed of presumptive tonic, slow twitch and intermediate fibres, thickening to a major wedge at the horizontal septum. All species also had characteristic secondary dorsal and ventral wedges of red muscle. The relative abundance and localization of muscle fibre types in the red muscle varied between species and with body size in the protandric hermaphrodite E. maclovinus. The frequency distribution of diameters for fast twitch muscle fibres, the major component of deep white muscle, was determined in fish of a range of body sizes. The absence of fibres <20 mu m diameter was used as a criterion for the cessation of muscle fibre recruitment. Fibre recruitment had stopped in P, tessellata of 13.8 cm L-T and E, maclovinus of 32.8 cm L-T, equivalent to 49 and 36.5% of their recorded maximum sizes respectively. As a result in 20-cm P. tessellata, the maximum fibre diameter was 300 mu m and 36% of fibres were in excess of 200 mu m The unusually large maximum fibre diameter, the general arrangement of the red muscle layer and the extreme pH lability of the mATPase of fast twitch fibres are all common characters of the sub-Antarctic and Antarctic Notothenioids, including Cottoperca gobio, the suggested sister group ...